Pierce, B. B., Ranch and Residence, Los Osos Valley, San Luis Obispo County; Warden, L.M., Dairy Ranch and Residence, Los Osos Valley, San Luis Obispo County [On Same Plate] (1883)
Hand-tinted lithographs.